The Fibularis Quartus Muscle: A Cadaveric Case Report with Historical, Embryological, Molecular and Clinical Considerations - Dibakar Borthakur; Rajesh Kumar; Namaschivayam G R; Mohammed Ahmed Ansari; Seema Singh (Acta Medica Lituanica)
Introduction: The fibularis quartus (FQ) or peroneus quartus (PQ) is a supernumerary muscle occasionally seen in the lateral compartment of the human leg. It is a weak evertor and has a role in pronation and lateral stabilization of the foot. FQ arises from the fibularis brevis (FB) in most instances and distally gets attached to the lateral aspect of the base of the fifth metatarsal or the cuboid or the calcaneus bone. The muscle has been implicated in a variety of clinical problems ranging from ankle pain to subluxation and tear of peroneal tendons. We report here a rare bitendinous variant of FQ which might provide new insight to clinical problems related to the presence of this muscle and its possible utility as an autograft in reconstruction. Methods: Institutional guidelines for use of human cadaver were followed. Routine dissection was performed on a 71-year-old male donated cadaver in both the lower limbs. Gross anatomical features were meticulously noted, photographed and measurements were recorded with digital Vernier callipers. Results: A bitendinous muscle was observed in the lateral compartment of the left leg and identified as FQ. The FQ was proximally attached to the FB and adjacent distal third of the fibula, which then formed a flat fusiform muscle belly and eventually terminated through a rounded tendon via its attachment to the peroneal trochlea of the calcaneus. The dimensions of the proximal tendon, muscle belly and the distal tendon were 4.2 cm x 0.7 cm, 5.6 cm x 1.9 cm and 2.6 cm x 0.3 cm, respectively. Conclusions: Clinicians should be aware about all possible variants of the supernumerary FQ muscle considering its role in several lateral ankle pathologies. FQ can prove as an excellent autograft for peroneal tendon tear and can be utilized for strengthening weakened peroneal tendons.